How do pregnant women and new mothers navigate and respond to challenges in accessing health care? Perspectives from rural South Africa. (August 2020) - Laurenzi, Christina A.; Skeen, Sarah; Coetzee, Bronwyne J.; Gordon, Sarah; Notholi, Vuyolwethu; Tomlinson, Mark
Abstract: Women in low- and middle-income countries and in contexts characterized by inequality face various interpersonal and structural barriers when accessing formal maternal and child health (MCH) services. These barriers persist even in contexts where programs to increase access to services, such as community health worker (CHW) interventions, have been implemented. However, while barriers to accessing care have been extensively documented, less is known about the diverse ways that women respond to, and navigate, these situations. This study explores strategies pregnant women and new mothers use to navigate and respond to health care barriers in a rural district in the Eastern Cape, South Africa. Twenty-six pregnant or recently delivered clients of the Enable Mentor Mother program were interviewed about their experiences of accessing formal MCH services. Interviews were conducted between February-March 2018 by an experienced isiXhosa-speaking research assistant, translated and transcribed into English, with transcripts coded and organized by themes using ATLAS.ti software. Facing resource shortages, inconsistent communication, and long travel times to clinics, participants employed diverse, innovative strategies to navigate interpersonal and structural barriers to care. While some participants chose to respond to barriers more passively—citing endurance and acceptance as practices of health system engagement—those participants who focused more on active responses tended to leverage their education, existing relationships, and available community resources to overcome barriers. Nevertheless, most participants described feelings of frustration and dejection. While CHW interventions may alleviate some of the burdens facing fragile health care systems in these contexts, these programs still rely on an underlying infrastructure of care that primary health care clinics and hospitals should be providing. Future programming should work in tandem with formal health systems and should support staff to improve quality of care provided to pregnant women, new mothers, and their infants to prioritize their health at a time of vulnerability. Highlights: Passive and assertive approaches were common responses to health access barriers. Pregnant women and new mothers leveraged internal and community support resources. Women felt less motivated to access care following repeated systemic failings. Community health programs have limited impact when facing larger-level challenges.